Extensive Sodium Metal Plating and Stripping in a Highly Concentrated Inorganic−Organic Ionic Liquid Electrolyte through Surface Pretreatment. Issue 5 (23rd February 2017) - Basile, Andrew; Makhlooghiazad, Faezeh; Yunis, Ruhamah; MacFarlane, Douglas R.; Forsyth, Maria; Howlett, Patrick C.
Abstract: In the present work, the stable and extensive cycling of Na plating and stripping is demonstrated within an inorganic−organic ionic liquid electrolyte. The electrolyte is composed of liquid‐state tri(isobutyl)methylphosphonium bis(fluorosulfonyl)imide when employing a high 45 mol % Na concentration in the form of sodium bis(fluorosulfonyl)imide. The liquid‐state electrolyte supports safe Na metal electrochemistry at 50 °C and exhibits a conductivity of 10 −2.5  S cm −1 . Through plating/stripping with 1 h polarization times (12 cycles, J =0.5 mA cm −2 ), a surface is prepared with a smooth surface devoid of dendrites and, importantly, a stable solid‐electrolyte interphase, determined by using scanning electron microscopy and impedance spectroscopy. After this, a greater mass transfer can be undertaken through an increased polarization time of 5 h (Q=2.5 mAh cm −2 ) for a duration of 120 h. Abstract : Aim high : An initial high potential during the primary half cycle is absent upon opposite polarization when using a pre‐cycled Na foil in a Na|Na cell comprising a highly concentrated 45 mol % NaFSI in tri(isobutyl)methylphosphonium bis(fluorosulfonyl)imide electrolyte. Successive cycles at 2.5 mAh cm −2 (5 h half cycle, J =0.5 mA cm −2 ) provide a stable voltage‐time profile, a smooth surface morphology and decreased interfacial resistance.